Education Challenges to Thailand 4.0 - Wittayasin, Supakit (International Journal of Integrated Education and Development, 2018)
The article provided framework of Thailand 4.0 which is a new economic model for Thailand. Thailand needs education reform to pull the country out of the Thailand 3.0 trap. The education challenges to Thailand 4.0 were also pointed out. Poor quality education and education inequality are two main educational problems which need a serious consideration.